2021
DOI: 10.3389/fchem.2021.705024
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Structural Modelling of Non-Stoichiometric Ln-Doped UO2 Solid Solutions,Ln = {La, Pr, Nd, Gd}

Abstract: Available data on the dependence of the equilibrium chemical potential of oxygen on degrees of doping, z, and non-stoichiometry, x, y, in U1-zLnzO2+0.5(x-y) fluorite solid solutions and data on the dependence of the lattice parameter, a, on the same variables are combined within a unified structural-thermodynamic model. The thermodynamic model fits experimental isotherms of the oxygen potential under the assumptions of a non-ideal mixing of the endmembers, UO2, UO2.5, UO1.5, LnO1.5, and Ln0.5U0.5O2, and of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 79 publications
1
12
0
Order By: Relevance
“…Recent computational studies on lanthanide-doped UO 2 [22] have shown that trivalent cation size influences oxidation, in that the strain associated with small cations results in stabilization from further contraction upon oxidation; this result is supported by our previous investigations where Yb:UO 2 showed delayed oxidation compared with Nd:UO 2 . [1] In the case here, there may be a different effect, because Zr is considerably smaller than Th and results in worse oxidation, but the charge compensation mechanism is not present, so the effects of oxygen vacancies and interstitials will be different for the tetravalent dopants.…”
Section: In Situ Heat Stage Ramansupporting
confidence: 78%
See 2 more Smart Citations
“…Recent computational studies on lanthanide-doped UO 2 [22] have shown that trivalent cation size influences oxidation, in that the strain associated with small cations results in stabilization from further contraction upon oxidation; this result is supported by our previous investigations where Yb:UO 2 showed delayed oxidation compared with Nd:UO 2 . [1] In the case here, there may be a different effect, because Zr is considerably smaller than Th and results in worse oxidation, but the charge compensation mechanism is not present, so the effects of oxygen vacancies and interstitials will be different for the tetravalent dopants.…”
Section: In Situ Heat Stage Ramansupporting
confidence: 78%
“…[ 21 ] The effect of dopants, which in fuels may be fission products, on the oxidation behavior of UO 2 has been shown to be significant and variable with the dopant. [ 1,16,22 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, much less H 2 O 2 is consumed for the oxidation of UO 2 due to doping with trivalent Nd 3+ ions. It seems that the doping of Nd 3+ is stabilising the UO 2 structure and prevent U(+ IV) from oxidation [16].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, increasing the number of oxygen vacancies induces a reduction of An(IV) to An(III) to keep electroneutrality. These trivalent cations trap the oxygen vacancies, forming uncharged cluster defects (Anderson, 1971;Ando and Oishi, 1983;Bevan et al, 1986;Nakayama and Martin, 2009;Yoshida et al, 2011;Vinograd, Bukaemskiy, Modolo, Deissmann, Bosbach).…”
Section: Oxygen/metal Ratio Oxygen Potential Points Defects Clusters ...mentioning
confidence: 99%